Prevalence of, and factors associated with oral sexual behaviours in men and women in Ibadan, Nigeria - Imran Oludare Morhason-Bello; Adekunle Daniel; Akinyele Adisa; Kathy Baisley; Isaac Adewole; Rasheed Bakare; Robert Murphy; Lifang Hou; Silvia de Sanjosé; Suzanna C. Francis; Deborah Watson-Jones (PLoS ONE, 2025)
Background Unprotected oral sex is associated with sexually transmitted infections (STIs) including HPV and associated head and neck cancers. However, many studies lack clear definitions of oral sex and there are few data from West Africa. This study assessed the pattern and prevalence of, and factors associated with oral sex among Nigerian men and women from the general population. Methods The Sexual Behaviours and HPV Infections in Nigerians in Ibadan (SHINI) study was a cross-sectional study conducted among men and women aged 18–45 years. Information on oral sexual behaviours was collected during a face-to-face interview by a sex-matched interviewer. Descriptive and multivariable analyses were used to analyse factors associated with oral sex in men and women. Results In total, 160/626 (26%) had ever any type of oral sex. Specifically, 78/626 (12%) had ever given and 139/626 (22%) had ever received oral sex in a heterosexual relationship. Overall, 35% (112/310) men had ever engaged in oral sex compared to women 15% (48/316 –p < 0.001). More men frequently reported ever receiving oral sex than women (33% vs. 12%; p < 0.001). There was no difference in the proportion of men and women that reported ever giving oral sex. Most (94%) participants never used any barrier protection during oral sex. Most men and women participants engaged in oral sex because of romantic relationship or being married. In the adjusted models, there was a higher odds of ever receiving oral sex (Adjusted odds ratio = AOR 4.01 95% CI 2.52–6.38) or engaging in any form of oral sex (AOR = 3.12, 95%CI 2.04–4.76) in men than women. Conclusion Though, Nigerian men and women engage in oral sex in heterosexual relationship, but it is more commonly reported by men than women and most of them practiced it without barrier protection. It is recommended that sexually active men and women are counselled on risks associated with unprotected oral sex including STIs, HIV and HPV and associated cancers.